Descending paralysis as an atypical presentation of Guillain–Barré Syndrome. (January 2021) - Mustafa, Ala; Adio, Babajide; Yarahmadi, Alireza
We herein report a case of a 55-year-old man with an unusual case of Guillain–Barré Syndrome. Its presentation is usually a progression of symmetric muscle weakness that is ascending from the lower extremities making its way more proximal and accompanied by absent or depressed tendon reflexes. Here, the patient exhibited a rare presentation of Guillain–Barré syndrome, where the weakness was ascending upper extremity and descending lower extremity paralysis. The objective of this clinical case report is to highlight this extremely rare descending paralysis presentation of Guillain–Barré Syndrome.